Doppler middle cerebral artery peak systolic velocity measurement as diagnostic tool for fetal anemia after in utero transfusions in red blood cell alloimmunisation - Marjanović Cvjetićanin, Mirjana; Plešinac, Snežana; Dotlić, Jelena; Plećaš, Darko; Kocijančić Belović, Dušica; Akšam, Slavica (Vojnosanitetski pregled, 2021)
Background/Aim. Doppler sonography of fetal middle cerebral artery peak systolic velocity (MCA-PSV) can be used to predict fetal anemia and the need for in utero intravascular transfusion (IUIT) in red blood cell (RBC) alloimmunisation pregnancies. The aim of this study was to evaluate whether measurement of MCA-PSV in fetuses that had undergone one to three transfusions is a good diagnostic tool for fetal anemia. Methods. Study included 36 pregnancies treated due to RBC alloimmunisation in our tertiary referral center during the 5-year period (2012–2017). We measured MCA-PSV and hematocrit (Hct) in all patients. In seven pregnancies there was a need to perform sequential IUITs for correction of fetal anemia. In these patients we compared MCA-PSV and Hct values before and after every transfusion. Results. Hct and MCA-PSV correlated negatively before transfusion therapy (p = 0.035) and after the second transfusion (p = 0.046). Contrary, after the first (p = 0.954), before the second (p = 0.738), as well as before (p = 0.092) and after (p = 0,741) the third transfusions there were no significant correlations between Hct and MCA-PSV values. Hct values before and after transfusions were positively associated (p = 0.001), but MCA-PSV were not (p = 0.296). According to performed receiver operating characteristic (ROC) analysis the cut-off point of MCA-PSV for investigated patients was 1.22 multiples of its median (MoM). Conclusion. There is a reduction in MCA-PSV accuracy for assessing fetal anemia in previously transfused fetuses. Larger studies are needed to explain the reasons for these findings and potentially set new referral values of MCA-PSV for better diagnostics of fetal anemia.
Keywords: fetus; anemia; blood transfusion, intrauterine; blood group incompatibility; rh-hr blood group system; ultrasonography; hematocrit